Repair method suitable for shaft integrity casing cement sheath gap
By changing the wetting properties of the oil and gas well casing and cement ring gap surfaces and using modified resin-based repair of the sealing slurry, the problem of poor gap repair effect in the prior art is solved, and effective repair of gaps of ≤5mm and Long-term stability improves repair effect and mechanical properties.
Patent Information
- Application Number
- CN202411348986.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is not effective in repairing oil and gas well casing and cement ring gaps, especially micro-cracks that cannot be effectively repaired ≤5mm, and conventional cement materials cannot enter the micro-pores, and the stability after curing is poor, so long-term effects cannot be guaranteed. Effect.
The surface treatment liquid is used to change the wettability of the casing/cement ring gap surface, and the modified resin-based repair sealing slurry is repaired. The continuous oil pipe pumping repair sealing slurry is ensured to penetrate deep into the gap and solidify, and the modified double-degree Phenol A type epoxy resin, graphene modified phenolic resin and other materials improve bonding effect and mechanical properties.
It realizes effective repair of gaps of ≤5mm, has excellent mechanical properties after curing of repair and sealing slurry, can maintain long-term stability in various environments, ensures repair effect, and is suitable for temperature conditions of 25-150℃. .
Smart Images

Figure CN119221863A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas well plugging and oil and gas production, and in particular to a method for repairing a cement ring gap of a casing suitable for improving the integrity of a wellbore. Background Art
[0002] In the process of oilfield development, casing and cement sheath damage is a common problem, usually caused by formation water corrosion, casing wear, fracture, thread failure, casing defects and casing equipment failure. The problem of annular pressure caused by casing and cement sheath damage is becoming increasingly prominent. At present, the treatment of annular pressure wells in engineering mostly adopts regular detection, diagnosis and identification of gas sources and leaks, periodic pressure release, well repair and cement squeezing.
[0003] Long-term testing and depressurization of oil and gas wells poses huge safety risks. At the same time, the use of cement squeezing methods has certain shortcomings. The particle size of conventional cement is usually above 10μm, which cannot enter the micro-cracks and pores. In addition, cement shrinks after curing and has poor stability, which cannot guarantee long-term effects. However, resin systems such as epoxy resins, phenolic resins, furan resins, etc., due to the characteristics of completely containing no solid phase, can penetrate into micro-cracks to form a wider range of cementation. At the same time, resin materials also show high salt resistance, acid resistance and oil resistance, strong compressive resistance, and long effective period.
[0004] Invention patent CN116102845A provides a graphene-modified phenolic resin-based casing repair material and its preparation method. The repair material is composed of phenolic resin, diluent, graphene and cross-linking initiator. Under the action of the cross-linking initiator, graphene cross-links the phenolic resin. The cross-linked and cured phenolic resin material forms a maze effect, which has the advantages of high strength, high modulus, hydrolysis resistance, corrosion resistance, long-term stability, etc. However, the repair material has high viscosity and contains solid phase particles, which cannot enter the micro-cracks of the casing and are not suitable for repairing cracks ≤5mm. At the same time, the repair material is only suitable for casing repair, which has application limitations. Summary of the invention
[0005] In order to solve the problem that the existing repair technology has poor sealing effect on the casing / cement ring gap, the present invention provides a repair method for the casing cement ring gap suitable for wellbore integrity, which can be applied to the repair of the casing / cement ring gap size ≤5mm.
[0006] The present invention is achieved by adopting the following technical solutions.
[0007] A method for repairing cement ring gaps in casing for wellbore integrity, comprising the following steps:
[0008] S1. Pre-treat the gap section of the casing or cement ring to fully expose the leak point;
[0009] S2. Pump the surface treatment liquid to the leak point through the coiled tubing, circulate and clean the gap, change the wettability of the casing / cement ring gap surface, prepare the repair plugging slurry on site, pump all the plugging slurry to fully cover the leak point, wait until the liquid level inside and outside the coiled tubing is flush, pull the coiled tubing to 30-50m above the theoretical liquid level of the repair plugging slurry, continue to use the surface treatment liquid to push the repair plugging slurry deep into the leak point, observe the change of the squeeze pressure, record the squeeze volume, if the squeeze pressure reaches the set pressure (the pressure is determined according to the specific situation of each well), stop squeezing and remove all the coiled tubing;
[0010] S3. Shut down the well and hold the pressure.
[0011] By adopting the above technical scheme, the wettability of the surface of the casing / cement ring gap is changed by the surface treatment liquid, the contact ability between the repair sealing slurry and the casing / cement ring gap is improved, the bonding effect between the repair sealing slurry and the casing / cement ring is guaranteed, and at the same time, the repair sealing slurry exhibits excellent mechanical properties after curing, ensuring the repair effect.
[0012] Furthermore, in step S1, for the casing gap, conventional workover fluid is used to clean the inner surface of the casing, and the covering on the inner surface of the casing is removed by drilling and milling technology to fully expose the casing gap; for the cement ring gap, holes are opened on the casing surface by perforating method, and the opening positions are above and below the cement ring gap position to fully expose the cement ring gap; if the casing cement ring gap is not at the bottom of the well, the packer is lowered to 10-30m below the leakage point, and the above casing gap / cement ring gap treatment method is repeated.
[0013] Furthermore, conventional well repairing fluid is water + 0.3% sodium carboxymethyl cellulose.
[0014] Furthermore, the surface treatment liquid is formed by emulsifying epoxy resin, melamine, oleic acid, potassium hydroxide, propylene oxide and acetic acid in a certain proportion.
[0015] Furthermore, the preparation method of the surface treatment liquid is as follows: the epoxy resin and melamine are stirred and mixed evenly, the temperature is raised to 140-160° C., and then oleic acid is added for reaction, and potassium hydroxide is added and vacuum is applied when the epoxy value of the system no longer changes; the temperature is raised to 170-190° C., propylene oxide is continuously added, and the reaction is continued until the pressure in the reaction system is negative and the pressure no longer changes; the heating is turned off, the circulation cooling is performed until the system temperature drops to 50-70° C., acetic acid is added to adjust the pH of the system to 6-7, and a surface treatment liquid is obtained; wherein the mass ratio of the epoxy resin, melamine, oleic acid, potassium hydroxide, and propylene oxide is 1:0.0005-0.01:1-3:0.0001-0.01:0.5-1.5.
[0016] Furthermore, the repair and plugging slurry is composed of a repair main agent, a curing agent and a retarder. The amount of each component is: 100 parts of the repair main agent, 0.5-1.5 parts of the curing agent and 0-3 parts of the retarder by weight.
[0017] Furthermore, the main repair agent is selected from one or more of modified bisphenol A epoxy resin, graphene modified phenolic resin, and polyurethane modified epoxy resin.
[0018] The modified bisphenol A epoxy resin of the present application is modified according to the method described in the document "Research on low-viscosity organosilicon-modified bisphenol A epoxy resin" (Sun Shangyan; Zhang Xiyu; Wei Wei; Liu Xiaoya; Li Xiaojie. Research on low-viscosity organosilicon-modified bisphenol A epoxy resin. Thermosetting resins. 2022, Issue 5, pp. 7-13);
[0019] The graphene-modified phenolic resin of the present application is modified according to the method described in the document "Graphene / SiO2 hybrid nanoparticles modified phenolic resin and its properties" (Li Hui. Graphene / SiO2 hybrid nanoparticles modified phenolic resin and its properties. Modern Plastic Processing Applications. Issue 06, 2023);
[0020] The polyurethane modified epoxy resin of the present application is modified according to the method described in the document "Study on Polyurethane Modified Epoxy Resin" (Hu Jiapeng; Xiong Lianming; Shen Zhen; Zhou Wei. Study on Polyurethane Modified Epoxy Resin. Journal of Nanchang Hangkong University: Natural Science Edition. Issue 4, 2005, pp. 20-26).
[0021] Furthermore, the curing agent is selected from one or more of diaminodiphenylmethane, diaminodiphenyl ether, diethyltoluenediamine, and o-toluenediamine.
[0022] Furthermore, the retarder is selected from one or more of tartaric acid, glycidyl methacrylate, ethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, and organic phosphate.
[0023] Furthermore, the repair and plugging slurry has a viscosity of 100-200 cP at room temperature and a density of 1.0-1.10 g / cm 3 The curing time is 3-24h. After curing, the compressive strength is ≥70MPa and the tensile strength is ≥25MPa.
[0024] Furthermore, in step S3, the shut-in and pressure-holding waiting time is 12-48 hours, and the pressure-holding pressure is 0.5-5.0 MPa.
[0025] It should be noted that, in the above-mentioned terms such as “casing gap / cement ring gap” or “casing / cement ring” in the present application, “ / ” means “or”.
[0026] This application has the following beneficial effects.
[0027] (1) The surface treatment liquid of the present invention has low viscosity and is easy to pump. At the same time, it can change the wettability of the surface of the casing / cement ring gap, which can indirectly improve the repair effect of the repair plugging slurry;
[0028] (2) The repair and plugging slurry of the present invention has no solid phase and low viscosity, and can penetrate into the gap between the casing and cement ring (gap size ≤ 5 mm). Its curing time can be controlled to be 3-24 hours. After curing, it has excellent mechanical properties and can maintain stable mechanical properties for a long time in various environments (formation water, high mineralization, strong acid, workover fluid, etc.), and the repair effect is obvious;
[0029] (3) The surface treatment liquid and the repair and plugging slurry of the present invention are non-corrosive and will not affect the properties of the undamaged casing / cement ring. In addition, the surface treatment liquid and the repair and plugging slurry have good compatibility and will not affect the performance of each other.
[0030] (4) The repair method of the present invention has a wide application temperature range and can be applied to repair operations under temperature conditions of 25-150°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a flow chart of on-site operation of repairing casing or cement ring gaps according to the present invention;
[0032] Figure 2 It is a stress-strain curve diagram of the repair and plugging slurry after solidification of Example 1 and Example 3 of the present invention (the stress-strain curve of the repair and plugging slurry after solidification of Example 1 is a dotted line, and the stress-strain curve of the repair and plugging slurry after solidification of Example 3 is a solid line). DETAILED DESCRIPTION
[0033] The present patent application is further described below in conjunction with embodiments.
[0034] Unless otherwise specified, the experimental methods used in the following preparation examples and embodiments are conventional methods.
[0035] Preparation Example
[0036] The surface treatment liquid preparation method is as follows: 500g of bisphenol A epoxy resin and 0.3g of melamine are stirred and mixed evenly in a reactor, the temperature is raised to 150°C, 600g of oleic acid is added to the reactor for reaction, the epoxy value of the system is tested, and the epoxy value no longer changes, and then 0.3g of potassium hydroxide is added to the reactor, and vacuum is applied; the temperature is raised to 180°C, 400g of propylene oxide is continuously added, and the reaction is continued until the pressure in the reactor is negative pressure and the pressure no longer changes; the heating is turned off, the reactor is circulated and cooled, the system temperature is reduced to 65°C, acetic acid is added to the reactor to adjust the pH of the system to 7, and the surface treatment liquid is prepared.
[0037] Example 1
[0038] The formula of repair plugging slurry is: 100g modified bisphenol A epoxy resin, 1.5g diaminodiphenylmethane. The plugging slurry was prepared according to the formula, and the curing time of the plugging slurry at 25°C and the mechanical properties after curing were tested according to the GB10238-2005 "Oil Well Cement" standard. The test results showed that the curing time was 3.5h, the compressive strength after curing was 78.15MPa, and the tensile strength was 28.56MPa. The viscosity of the repair plugging slurry at 25°C was tested according to the GB / T 11145-2014 "Determination of Low-temperature Viscosity of Lubricants - Brokfeldt Viscometer Method" standard, and the test result was 120cP.
[0039] Example 2
[0040] The formula of repair plugging slurry is: 100g modified bisphenol A epoxy resin, 1g diethyltoluenediamine, 0.3g glycidyl methacrylate. The plugging slurry is prepared according to the formula. The curing time of the plugging slurry at 80°C and the mechanical properties after curing are tested according to the GB10238-2005 "Oil Well Cement" standard. The test results show that the curing time is 5h, the compressive strength after curing is 80.38MPa, and the tensile strength is 29.17MPa. According to the GB / T 11145-2014 "Determination of Low-temperature Viscosity of Lubricants - Brokfeldt Viscometer Method" standard, the viscosity of the repair plugging slurry at 25°C is tested, and the test result is 125cP.
[0041] Example 3
[0042] The formula of repair plugging slurry is: 100g modified bisphenol A epoxy resin, 0.8g diaminodiphenyl ether, 1g ethylene glycol diglycidyl ether. The plugging slurry was prepared according to the formula, and the curing time of the plugging slurry at 120°C and the mechanical properties after curing were tested according to the GB10238-2005 "Oil Well Cement" standard. The test results showed that the curing time was 4h, the compressive strength after curing was 82.91MPa, and the tensile strength was 29.56MPa. The viscosity of the repair plugging slurry at 25°C was tested according to the GB / T 11145-2014 "Determination of Low-temperature Viscosity of Lubricants - Brokfeldt Viscometer Method" standard, and the test result was 122cP.
[0043] Example 4
[0044] The formula of repair plugging slurry is: 100g modified bisphenol A epoxy resin, 0.4g diaminodiphenyl ether, 2.5g trimethylolpropane triglycidyl ether. The plugging slurry was prepared according to the formula, and the curing time of the plugging slurry at 150°C and the mechanical properties after curing were tested according to the GB10238-2005 "Oil Well Cement" standard. The test results showed that the curing time was 6.5h, the compressive strength after curing was 83.12MPa, and the tensile strength was 29.93MPa. The viscosity of the repair plugging slurry at 25°C was tested according to the GB / T 11145-2014 "Determination of Low-temperature Viscosity of Lubricants - Brokfeldt Viscometer Method" standard, and the test result was 120cP.
[0045] The invention is applicable to a method for repairing cement ring gaps in casing of wellbore integrity, and the steps are as follows: firstly, pre-treating the casing or cement ring gap section to fully expose the leakage point, then pumping the surface treatment liquid to the leakage point through the continuous oil pipe, circulating and cleaning the gap, changing the wettability of the surface of the casing / cement ring gap, preparing the repair and plugging slurry on site, pumping all the repair and plugging slurry to fully cover the leakage point, waiting for the liquid levels inside and outside the continuous oil pipe to be flush, raising the continuous oil pipe to 30-50m above the theoretical liquid level of the repair and plugging slurry, continuously pushing the repair and plugging slurry with the surface treatment liquid to penetrate into the leakage point, observing the change of the squeezing pressure, recording the squeezing amount, and if the squeezing pressure reaches the set pressure, stopping the squeezing, taking out all the continuous oil pipes, shutting down the well to hold the pressure and wait for solidification.
[0046] Performance Testing
[0047] (1) Simulated casing crack repair evaluation experiment
[0048] The hollow steel pipe is artificially made to penetrate cracks (crack width is 3-5mm) to simulate the damaged casing, wherein the inner diameter of the hollow steel pipe is 50mm, the length is 200mm, the lower end is closed, and the upper end has threads, and the displacement / pressure test pipeline is connected by threads. The repair effect of the surface treatment liquid and the slurry of Example 2 is tested. First, the hollow steel pipe is immersed in the surface treatment liquid / water for 2h, taken out, connected to the displacement pipeline, and the repair plugging slurry prepared in Example 2 is poured into the displacement device, and the plugging slurry is squeezed into the hollow steel pipe through the displacement device. After the plugging slurry penetrates from the crack, the squeezing is stopped, taken out, the upper end of the steel pipe is sealed, and placed in an 80℃ oven for 24h, and the drill plug is drilled to the lower part of the casing crack to fully expose the repair part, and then the pressure test pipeline is connected, and the gradient is increased by 0.5MPa every 10 minutes. The leakage at the crack of the steel pipe is observed to judge the repair effect. The experimental results are shown in Table 1.
[0049] Table 1 Experimental results of simulated casing gap repair effect
[0050]
[0051]
[0052] It can be seen from Table 1 that the surface treatment liquid and the repair and plugging slurry must work together to achieve the best repair effect. Using the repair and plugging slurry alone can achieve a certain repair effect, but the effect is not obvious. This is because the surface treatment liquid can enhance the bonding effect between the repair and plugging slurry and the surface of the casing gap.
[0053] (2) Cement ring gap repair evaluation experiment
[0054] A core flow test device (core displacement device, purchased from Qingdao Haitongda Special Instrument Co., Ltd.) was used to test the changes in the squeeze pressure of the cement column before and after the surface treatment liquid and the repair plugging slurry were repaired. The solidified cement stone was cut into a cylinder with a diameter of 25 mm and a length of 50 mm. A through hole with a diameter of 5 mm was opened in the middle of the cylinder. The cement column was placed in the test device and connected to the displacement pipeline. The surface treatment liquid / water was first displaced. After 10 minutes of displacement, the repair plugging slurry prepared in Example 2 was displaced. When the amount of repair plugging slurry to be displaced reached 80 mL, the displacement was stopped, and the test device of the cement column was placed in an 80°C oven for 24 hours of solidification. It was taken out and connected to the pressure test pipeline to record the squeeze pressure.
[0055] Table 2 Experimental results of cement ring gap repair effect
[0056] Serial number Repair system Squeeze pressure before repair MPa Squeeze pressure after repair MPa 1 Surface treatment liquid + Example 2 0.2 24 2 Water + Example 2 0.2 10 3 Untreated + Example 2 0.2 12 4 Surface treatment liquid + water 0.2 0.2
[0057] Note: 24MPa is the maximum pressure allowed for the operation of the experimental instrument.
[0058] As shown in Table 2, after the surface treatment liquid and the repair plugging slurry were used to repair the cement ring gap, the squeeze pressure was ≥24MPa, and no leakage occurred, indicating that all cracks and voids in the cement column had been filled and repaired by the repair plugging slurry. However, after the squeeze pressure of the cement column that was not treated with the surface treatment liquid reached a certain value, obvious leakage occurred, indicating that the surface treatment liquid played a key role in this repair method; by comparing the experimental results of the 1# and 4# systems, it can be seen that the surface treatment liquid alone does not have the repair ability, and it needs to be combined with the repair plugging slurry to achieve the repair effect.
[0059] In summary, the repair method of the present invention can be applied to the repair of casing / cement ring gaps with a size of ≤5mm. The wettability of the surface of the casing / cement ring gap is changed by the surface treatment liquid, thereby improving the contact ability between the repair plugging slurry and the casing / cement ring gap, ensuring the bonding effect between the repair plugging slurry and the casing / cement ring. At the same time, the repair plugging slurry exhibits excellent mechanical properties after curing, ensuring the repair effect, and solving the problem of poor casing / cement ring gap repair effect in the prior art.
[0060] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for repairing the cement ring gap of casing suitable for wellbore integrity, characterized by: The following steps are involved: S1. Pre-treat the gap section of the casing or cement ring to fully expose the leak point; S2. Pump the surface treatment liquid to the leak point through the coiled tubing, circulate and clean the gap, change the wettability of the casing / cement ring gap surface, prepare the repair plugging slurry on site, pump all the plugging slurry to fully cover the leak point, wait until the liquid levels inside and outside the coiled tubing are flush, pull the coiled tubing to 30-50m above the theoretical liquid level of the repair plugging slurry, continue to use the surface treatment liquid to push the repair plugging slurry deep into the leak point, observe the changes in the squeezing pressure, record the squeezing volume, if the squeezing pressure reaches the set pressure, stop squeezing and remove all the coiled tubing; S3. Shut down the well and hold the pressure.
2. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 1, characterized in that: In step S1, for the casing gap, conventional workover fluid is used to clean the inner surface of the casing, and the covering on the inner surface of the casing is removed by drilling and milling technology to fully expose the casing gap; for the cement ring gap, holes are opened on the casing surface by perforating method, and the opening positions are above and below the cement ring gap position to fully expose the cement ring gap; if the casing cement ring gap is not at the bottom of the well, the packer is lowered to 10-30m below the leakage point, and the above casing gap / cement ring gap treatment method is repeated.
3. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 1, characterized in that: The surface treatment liquid is prepared by emulsifying epoxy resin, melamine, oleic acid, potassium hydroxide, propylene oxide and acetic acid in a certain proportion.
4. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 3, characterized in that: The preparation method of the surface treatment liquid is as follows: epoxy resin and melamine are stirred and mixed evenly, the temperature is raised to 140-160° C., oleic acid is added for reaction, potassium hydroxide is added and vacuum is applied when the epoxy value of the system no longer changes; the temperature is raised to 170-190° C., propylene oxide is continuously added, and the reaction is continued until the pressure in the reaction system is negative and the pressure no longer changes; heating is turned off, circulating cooling is performed until the system temperature drops to 50-70° C., acetic acid is added to adjust the pH of the system to 6-7, and a surface treatment liquid is obtained; wherein the mass ratio of epoxy resin, melamine, oleic acid, potassium hydroxide and propylene oxide is 1:0.0005-0.01:1-3:0.0001-0.01:0.5-1.
5.
5. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 1, characterized in that: The repair and plugging slurry is composed of a repair main agent, a curing agent and a retarder. The amount of each component is: 100 parts of the repair main agent, 0.5-1.5 parts of the curing agent and 0-3 parts of the retarder by weight.
6. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 5, characterized in that: The main repair agent is selected from one or more of modified bisphenol A epoxy resin, graphene modified phenolic resin, and polyurethane modified epoxy resin.
7. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 5, characterized in that: The curing agent is selected from one or more of diaminodiphenylmethane, diaminodiphenyl ether, diethyltoluenediamine, and o-toluenediamine.
8. The method for repairing the cement ring gap of casing applicable to wellbore integrity according to claim 5, characterized in that: The retarder is selected from one or more of tartaric acid, glycidyl methacrylate, ethylene glycol diglycidyl ether, trimethylolpropane triglycidyl ether, and organic phosphate.
9. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 1 or 5, characterized in that: The repair and plugging slurry has a room temperature viscosity of 100-200 cP and a density of 1.0-1.10 g / cm 3 The curing time is 3-24h. After curing, the compressive strength is ≥70MPa and the tensile strength is ≥25MPa.
10. A method for repairing cement ring gaps in casing for wellbore integrity according to claim 1, characterized in that: In step S3, the well is shut down and the pressure is held down for a solidification time of 12-48 hours, and the pressure is held down for a time of 0.5-5.0 MPa.
